PENGUATAN DESENTRALISASI FISKAL MELALUI PENGATURAN PAJAK DAERAH: NASKAH AKADEMIK RAPERDA PAJAK DAERAH KOTA TANJUNGPINANG - Haula Rosdiana; - Inayati (InFestasi, 2012)
Ratification of amendments to the Law on Local Tax and Charges (Law PDRD) in august 2009 provides an opportunity for local governments to optimize the management of regional resources, including fiscal capacity building through strengthening local taxing power. This amendment provides a logical consequence for all local governments, including the City of Tanjungpinang to immediately formulate the draft of local tax regulation. This study is an academic text which is organized as a consideration in preparing the PDRD draft to the provisions proposed in the regulation draft which can be justified scientifically.This study applies an academic approach which is juridical and empirical normative, using primary and secondary data whereby the data collection techniques incorporates FGD as well. This study is presented on the form of accommodation provision of material and formal change of setting local tax on PDRD Act of 2009 in the draft of Municipal Government Tanjungpinang.  The form of accommodation changes is associated with the expansion of the material provisions of the tax object, setting the subject of taxes and tax rates. In addition, it is necessary for a formal tax-related settings to play a role in supporting the implementation of obligations and fulfillment of the rights of tax payers to refer to the KUP Act. This study also suggests a recommendation regarding the expansion of revenue base, strengthening tax collection, and increasing surveillance and efficiency in tax collection area.